Expression and function of the Kallikrein-related peptidase 6 in the human melanoma microenvironment - Krenzer, Stefanie; Peterziel, Heike; Mauch, Cornelia; Blaber, Sachiko I.; Blaber, Michael; Angel, Peter; Heß, Jochen (The journal of investigative dermatology, 2011)
Cutaneous malignant melanoma is an aggressive disease of poor prognosis. Clinical and experimental studies have provided major insight into the pathogenesis of the disease, including the functional interaction between melanoma cells and surrounding keratinocytes, fibroblasts, and immune cells. Nevertheless, patients with metastasized melanoma have a very poor prognosis and are largely refractory to clinical therapies. Hence, diagnostic tools to monitor melanoma development, as well as therapeutic targets, are urgently needed. We investigated the expression pattern of the kallikrein-related peptidase 6 (KLK6) in human melanoma tissue sections throughout tumor development. Although KLK6 was not detectable in tumor cells, we found strong KLK6 protein expression in keratinocytes and stromal cells located adjacent to benign nevi, primary melanomas, and cutaneous metastatic lesions, suggesting a paracrine function of extracellular KLK6 during neoplastic transformation and malignant progression. Accordingly, recombinant Klk6 protein significantly induced melanoma cell migration and invasion accompanied by an accelerated intracellular Ca2+ flux. We could further demonstrate that KLK6-induced intracellular Ca2+ flux and tumor cell invasion critically depends on the protease-activated receptor 1 (PAR1). Our data provide experimental evidence that specific inhibition of the KLK6-PAR1 axis may interfere with the deleterious effect of tumor-microenvironment interaction and represent a potential option for translational melanoma research.
Gesehen am 08.07.2022